Hubungan Sikap Sabar dengan Kebahagiaan Pada Ibu Yang Memiliki Anak Berkebutuhan Khusus Di SLB Negeri Lahat - Sovianti, Iis; Alkaf, Idrus; Rama Pri Handiki, Yulian (Program Studi Tasawuf dan Psikoterapi, 2024)
The purpose of this study was to determine the relationship between patience and happiness in mothers who have children with special needs in SLB Negeri Lahat. This study uses quantitative research using a form of field research in the form of a correlational research model. Data collection methods in this study using questionnaires with Likert scale score measurements. While the data analysis technique uses product moment correlation by Pearson with the help of the Statistical Program for Social Science (SPSS) version 25.0 for Windows program. The results of this study indicate a positive relationship between patience and happiness which shows a correlation of 0.746 and a significance of 0.000 <0.05 which means that the two variables have a relationship. This shows that the effective contribution of the patient attitude variable to the happiness variable is 74.6% while the other 25.4% is determined by other things that are not revealed in this study.